The Role of E-Commerce Technology for Entrepreneurial Success - Marlina, Reni; Bahri, Efri Syamsul (Yayasan Mitra Peduli Indonesia, 2024)
E-commerce has become essential for entrepreneurs to expand market access, increase operational efficiency, and reduce business costs. This study aims to analyze the role of e-commerce technology in increasing the success of entrepreneurs through a qualitative approach and literature study. The results of this study indicate that the role of e-commerce technology includes facilitating product innovation, personalizing services, and collecting more effective customer data. E-commerce technology also contributes to business competitiveness at the global level. In addition, the success of e-commerce adoption by entrepreneurs is determined by the readiness of digital competence and support from the government and various parties, including training and incentives. Entrepreneurs must optimize e-commerce technology to create added value and achieve sustainable business growth.